Glycaemic benefit of iGlarLixi in insulin‐naive type 2 diabetes patients with high HbA1c or those with inadequate glycaemic control on two oral antihyperglycaemic drugs in the LixiLan‐O randomized trial. Issue 8 (18th June 2019) - Davies, Melanie J.; Russell‐Jones, David; Barber, Thomas M.; Lavalle‐González, Fernando J.; Galstyan, Gagik R.; Zhu, Dalong; Baxter, Mike; Dessapt‐Baradez, Cecile; McCrimmon, Rory J.
Abstract: In this post hoc analysis of the randomized controlled LixiLan‐O trial in insulin‐naive patients with type 2 diabetes mellitus (T2DM) not controlled with metformin, with or without a second oral antihyperglycaemic drug (OAD), the efficacy and safety of the fixed‐ratio combination, iGlarLixi (insulin glargine 100 U [iGlar] and lixisenatide [Lixi]), compared to its individual components was assessed in two patient subgroups: group 1) baseline HbA1c ≥9% ( n = 134); group 2) inadequate control (HbA1c ≥7.0% and ≤9.0%) despite administration of two OADs at screening ( n = 725). Treatment with iGlarLixi resulted in significantly greater reduction in least squares mean HbA1c compared to treatment with iGlar or Lixi alone in both subgroups (group 1: 2.9%, 2.5%, 1.7% and group 2: 1.5%, 1.2%, 0.7%, respectively). Target HbA1c less than 7% was achieved in more than 70% of patients using iGlarLixi in both subgroups, while mitigating the weight gain observed with use of iGlar alone. Rates of hypoglycaemic events were low overall. These results suggest that treatment with iGlarLixi achieves superior glycaemic control compared to treatment with iGlar or Lixi alone in T2DM patients with HbA1c ≥9% or in those inadequately controlled with two OADs.